2018
DOI: 10.1038/s41598-018-24772-7
|View full text |Cite|
|
Sign up to set email alerts
|

Exploring intrinsically disordered proteins in Chlamydomonas reinhardtii

Abstract: The content of intrinsically disordered protein (IDP) is related to organism complexity, evolution, and regulation. In the Plantae, despite their high complexity, experimental investigation of IDP content is lacking. We identified by mass spectrometry 682 heat-resistant proteins from the green alga, Chlamydomonas reinhardtii. Using a phosphoproteome database, we found that 331 of these proteins are targets of phosphorylation. We analyzed the flexibility propensity of the heat-resistant proteins and their speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 84 publications
1
23
0
Order By: Relevance
“…In Fungi and rest of Eukaryota, 14 and 6 species, respectively, stand out from the central cloud of data points with IDP fraction > 0.6 and IDR fraction > 0.2. Of these, six are Basidiomycota in Fungi, and, intriguingly, in the rest of Eukaryota we find 14 species all of which produce spores: 12 species of Apicomplexa, the choanoflagellate Salpingoeca rosetta (strain ATCC 50,818/BSB-021) and the single-cell green alga Chlamydomonas reinhardtii [ 31 ]). In Archaea there is a visibly distinct group containing species with high IDP and IDR fractions compared to the rest (IDP fraction > 0.2, IDR fraction > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…In Fungi and rest of Eukaryota, 14 and 6 species, respectively, stand out from the central cloud of data points with IDP fraction > 0.6 and IDR fraction > 0.2. Of these, six are Basidiomycota in Fungi, and, intriguingly, in the rest of Eukaryota we find 14 species all of which produce spores: 12 species of Apicomplexa, the choanoflagellate Salpingoeca rosetta (strain ATCC 50,818/BSB-021) and the single-cell green alga Chlamydomonas reinhardtii [ 31 ]). In Archaea there is a visibly distinct group containing species with high IDP and IDR fractions compared to the rest (IDP fraction > 0.2, IDR fraction > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms whereby RNA (and possibly proteins) are stabilized/protected during desiccation (Figures and ) are as yet unknown. IDPs were implicated in the revival of Milnesium tardigradum following desiccation (Boothby et al, ) and in various algal activities (Gontero & Maberly, ; Niklas, Dunker, & Yruela, ; Zhang, Launay, Schramm, Lebrun, & Gontero, ). Many of the genes most strongly up‐regulated during early dehydration encode small, highly disordered, charged proteins.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been shown that the activity of Calvin-Benson-Bassham (CBB) cycle enzymes is strongly affected by high pressure [61]. IDPs, which are devoid of internal cavities, are expected to be more stable upon pressure increase, and indeed, -synuclein [62] and the disordered region of titin [63] In the model alga Chlamydomonas reinhardtii, a systematic search for disordered protein experimentally showed that this alga contains a large number of non-characterised proteins that have IDP-like properties [72]. Interestingly, the few IDPs that have been biophysically investigated so far are the ones involved in the regulation of their metabolic pathways.…”
Section: Idp In Plants and Algaementioning
confidence: 99%
“…An experimental search for IDPs in C. reinhardtii showed that chaperones and ribosomal proteins were the most represented IDPs [72]. Twenty proteins related to chaperone-function were identified, such as the heat-shock proteins HSP33, HSP40, HSP70s, FKBP, HSP90 co-chaperone, ….…”
Section: Molecular Chaperonesmentioning
confidence: 99%
See 1 more Smart Citation